The Effect of Ultrasonic Treatment on Some Functional Properties of Egg White. - Gélvez-Ordoñez, Victor Manuel; Mendoza-Galvis, Franklin; Orlando Delgado, Javier (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Â  This work studied the effect of treatment with a high frequency ultrasound bath (40 kHz and a power of 80 W.) on the pH, foaming capacity and stability of the foam of the white of hens eggs (sample 1/120 hours post laying and sample 2/24 hours post laying). Exposure time was at varied intervals of 0, 5, 10 and 15 mins at 20°C. The samples were stored in refrigeration at 4°C for 3 days. The comparative study of the data was carried out using variance analysis(ANOVA) and surface response analysis (RSA); where it was found that the pH did not show any significant changes(P